Low molecular weight poly(lactic acid) microparticles for controlled release of the herbicide metazachlor: preparation, morphology, and release kinetics - Stloukal, Petr; Kucharczyk, Pavel; Sedlarik, Vladimir; Bazant, Pavel; Koutny, Marek (Journal of agricultural and food chemistry, 2012)
The preemergence chloroacetamide herbicide metazachlor was encapsulated in biodegradable low molecular weight poly(lactic acid) micro- and submicroparticles, and its release to the water environment was investigated. Three series of particles, S, M, and L, varying in their size (from 0.6 to 8 μm) and with various initial amounts of the active agent (5%, 10%, 20%, 30% w/w) were prepared by the oil-in-water solvent evaporation technique with gelatin as biodegradable surfactant. The encapsulation efficiencies reached were about 60% and appeared to be lower for smaller particles. Generally, it was found that the rate of herbicide release decreased with increasing size of particles. After 30 days the portions of the herbicide released for its highest loading (30% w/w) were 92%, 56%, and 34% for about 0.6, 0.8, and 8 μm particles, respectively. The release rates were also lower for lower herbicide loadings. Metazachlor release from larger particles tended to be a diffusion-controlled process, while for smaller particles the kinetics was strongly influenced by an initial burst release.
Keywords: Herbicides; Particle Size; Acetamides; léky s prodlouženým účinkem; polymery; Drug Compounding; příprava léků; Delayed-Action Preparations; Lactic Acid; polyestery; acetamidy; Polymers; herbicidy; Kinetics; velikost částic; molekulová hmotnost; kinetika; Molecular Weight; Polyesters; kyselina mléčná